AUDIT KINERJA GURU DAN KEPALA SEKOLAH DI SMP MA'ARIF MIFTAHUL ULUM BUNGAH - Tria Heni Agustina; Amrozi Khamidi; Kaniati Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Republic of Indonesia Government Regulation Number 19 of 2005 concerning National Education Standards, article 2 paragraph 2, namely to guarantee and control the quality of education in accordance with national education standards, evaluation, accreditation and certification are carried out (President of the Republic of Indonesia, 2005). School Supervisors as functional technical implementers in the field of academic and managerial supervision in a number of designated educational units and have the main tasks of academic and managerial supervision, evaluation and auditing. Based on the audit results of the target school, Ma'arif Miftahul Ulum Middle School (foundation type institution), with the scope of academic and managerial audits in 2024. The main focus is the findings related to the results of the identification and analysis of the previous year's audit, the performance results of teachers and school principals rose to: predicate B